PERAN PENDIDIKAN AGAMA ISLAM DALAM MEWUJUDKAN KEADILAN DAN PERDAMAIAN DI INDONESIA - Azizah, Nurul (IAIN Ponorogo, 2013)
Abstract: The role of religious education in actualizing justice and peace in Indonesia has been going on for a long time, along with the advent of Islam in Indonesia. However, it does not mean the role is completely finished. It is widely asserted that there were still anarchic action, injustice, intolerance and other destructive actions happened. In this void, the study on the role of religious education in actualizing justice and peace is interesting to do. This research was aimed at seeking the new light on Islamic education that could be used as standards for the development of religious education in efforts to achieve peace in Indonesian. This study used a qualitative approach by employing in-depth interviews, participation observation, and documentation as data collection methods. TheÂ results ofÂ thisÂ studyÂ revealedÂ thatÂ firstly,Â religion has aÂ fundamental roleÂ inÂ the existence and continuity ofÂ Indonesian. Secondly,Â inÂ the era of regional autonomy and reformation, it was found that there was any significant improvement of the quality of religious education in which it was implemented consistently. Thirdly, in post-reformation, religious education took essential role as a place to build moral values of human resources to realize a sense of justice and peace in Indonesia.Â Ù ÙØ³ÙØ§ ÙÙØ®Ø¯ ÙÙØ® Ø¯ÙØ¹Ø¨ ÙØ§Ù Ø² Ø°ÙÙ Ø§ÙØ³ÙÙÙØ¯ÙØ¥ Ù Ù ÙØ³ÙØ§Ù Ø©ÙØ§Ø¯Ø¹ÙØ§ ÙÙÙØª Ù Ø©ÙÙÙØ¯ÙØ§ Ø©ÙØ¨ØªÙØ§ Ø±ÙØ¯ ÙØ§Ù :ØµØ®ÙÙ Â Ø©ÙØ§Ø¨ÙØ§ Ù Ø¯Ø¹Ù ØÙÙØ¹ÙØ§ Ø©Ø±ÙØ§Ø¸ Ø¡ÙØ´ÙØ¨ ÙÙØ°Ù .Ø¯ÙØ§ Ø§Ø°Ù ÙØ¥ ÙÙÙØªÙ Ù Ø±ÙØ¯ÙØ§ Ø§Ø°Ù ÙØ¥Ù ÙÙØ° Ù ØºØ±Ù .Ø§ÙØ³ÙÙÙØ¯ÙØ¥ ÙÂ Ø©ÙØ¨ØªÙØ§ Ø±ÙØ¯ Ù Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ§Ø²Øª ÙÙ .ÙÙ Ø¯ØªÙØ§Ù Ø¯Ø§Ø³ÙÙØ§ Ø©ÙÙÙ Ø¹ ÙØ¥ Ø©ÙØ¬ÙØªÙØ§ Ø©Ø·Ø´ÙÙØ§Ù ØØÙ Ø§Ø³ØªÙØ§ Ù Ø¯Ø¹Ù ØØ©ÙØ§Ø¯Ø¹ÙØ§Ø¨Â Ø©ÙØ¨ØªÙØ§ Ù Ø¯ÙØ¯ÙØ§ Ø¡ÙØ¶ÙØ§ Ø¡Ø§Ø·Ø¹Ù Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ØªÙØ±Ø¬Ø£ .Ø§ÙØ¨ Ù Ø§ÙÙÙÙ Ø©ÙÙØ´ Ù ÙØ³ÙØ§Ù Ø©ÙØ§Ø¯Ø¹ÙØ§ ÙÙÙØª Ù Ø©ÙÙ ÙØ³ÙØ§Â Ù Ù ÙØ³ÙØ§Â ÙÙÙØØªÙÂ Ø©ÙÙÙØ¯ÙØ§Â Ø©ÙØ¨ØªÙØ§Â Ø©ÙÙ ÙØªÙÂ Ø§Ø±Ø§ÙØ¹Ù Â ÙÙ ÙÙÙØªÂ ÙØ£Â ÙÙÙÙÂ ØØ©ÙÙ ÙØ³ÙØ§Â Ø©ÙØ¨ØªÙØ§Â Ø©ØµØ§Ø®ÙÂ Ø©ÙÙÙØ¯ÙØ§Â Ø©Ø¸ØÙÙØ§Ù ØØ©ÙÙÙ Ø¹ÙØ§ Ø©ÙØ¨Ø§ÙÙØ§ ÙÙØ±Ø· ÙØ¹ Ø§ÙØªØ§ÙØ§ÙØ¨ Ø¹Ø¬ Ø¨ÙÙØ³Ø£Ù ØØ©ÙÙØµÙ Ø©Ø³Ø§Ø±Ø¯ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù Ø¹ÙÙÙ .Ø§ÙØ³ÙÙÙØ¯ÙØ¥Â Ø¨Ø¹Ø´ÙØ§ Ø©ÙØ±Ø§Ø±Ù ØªØ³Ø§Ù Ø¯ÙØ¬Ù Ù ÙØ§Ù Ø¹Ù Ø±ÙØ¯ ÙÙØ¯ÙÙ )1 : Ø©ÙÙØ§ØªÙØ§ Ø¬Ø¦Ø§ØªÙÙØ§Ø¨ Ø«ØØ¨ÙØ§ ÙØªØ£ .Ø©Ø¨ÙØªÙÙØ§ ÙØ¦Ø§Ø«ÙÙØ§Ù ØØ©ÙØªØ´ÙØ§Â )3 ØØ±Ø§Ø±Ù ØªØ³Ø§Ø¨ Ø§ÙØªØ¯ÙØ¬ ØªÙ ÙØ±Øª Ø©ÙÙÙØ¯ÙØ§ Ø©ÙØ¨ØªÙØ§ Ø¹ÙØ§Ù ÙØ¥ ØÙØµÙØ§Ù Ø©ÙØ·ÙÙØ§ Ø©ÙÙÙÙØªØ³Ø§ Ø±ØµØ¹ ÙÙ )2 ØÙØ³ÙÙÙØ¯ÙÙØ§Â ÙØªØ Ø©ÙÙØªÙØ§ Ø©ÙØ±Ø´Ø¨ÙØ§ Ø¯Ø±Ø§ÙÙØ§Ù Ø©ÙØ±ÙÙØ§ ÙÙØ®ÙØ§ Ø©ÙÙ ÙØª Ø¹Ø¶ÙÙ Ø©ÙÙÙØ¯ÙØ§ Ø©ÙØ¨ØªÙØ§ ØªØØ¨ØµØ£ ØÙØÙØµÙØ§ Ø±ØµØ¹ÙØ§ Ø¯Ø¹Ø¨Ù.Ø§ÙØ³ÙÙÙØ¯ÙØ¥ Ù Ù ÙØ³ÙØ§Ù Ø©ÙØ§Ø¯Ø¹ÙØ§ ØªÙÙØª